Factors affecting the outcome of the usage of high-flow nasal cannula on severe or critically ill COVID-19 patients: a multicentric study from a developing nation (Asian Journal of Medical and Biological Research, 2021)
In resource-constrained settings, High-Flow Nasal Cannula (HFNC) can reduce the burden on mechanical ventilation in COVID-19 induced Acute Hypoxemic Respiratory Failure (AHRF). The aim was to observe the factors those might affect the outcome of the usage of HFNC on severe/critically ill COVID-19 patients. This is a multicentric prospective observational study. We observed rRT-PCR positive severe/critically ill ICU patients requiring HFNC for more than six hours. Statistical analysis was done to correlate between factors and outcome. Weaning from HFNC was successful in 47.5% of patients. The death rate was higher in ≥ 50 years older (56.50%), and patients with asthma (60.57%), COPD (60.00%), and CKD (68.42%). Fever (91.67%), cough (72.5%), and dyspnea (67.5%) were the most common symptoms. Mortality rates were higher for patients with raised blood sugar, creatinine levels. Severely systemic inflammatory response was seen very high for the expired patients. On HFNC, percent saturation of oxygen (SpO2) and partial pressure of oxygen (PaO2) progression was significantly high for the surviving patients requiring less inspired fraction of oxygen (FiO2%). The survival rate was higher for the patients using both HFNC and non-rebreather mask (NRM) concomitantly. While after HFNC- SpO2% and FiO2% were significantly related with outcome of the HFNC only treated patients, duration of hospital stay and on HFNC- FiO2% affected the HFNC + NRM treated patients’ outcome. HFNC could save more lives of critically ill AHRF patients who otherwise might need invasive or noninvasive ventilation. Some biochemical tests were observed to have association with the prognosis of the disease though HFNC was given to all. Survival benefit of dual HFNC and NRM therapy needs future study.Asian J. Med. Biol. Res. 2021, 7 (3), 260-272